Navigating the Tides of Change: A Comprehensive Analysis of Employment and Unemployment Dynamics in Indonesia. - Mulya, Nico Pranata (Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Labour dynamics are a central aspect of a country's economic growth. This study aims to conduct a descriptive analysis of the comparison of the working population and unemployment in Indonesia between 2011 and 2020. The data used is sourced from BPS statistical records, including the number of working population, the number of unemployed, and supporting variables such as wage rates, economic growth, employment opportunities, and education. Using a descriptive analysis approach, this study explores the main trends in the world of work over the past decade. Significant changes in the unemployment rate and working population were analysed to understand the impact of various factors, including the global economic crisis, technological changes, and the unprecedented pandemic. Findings reveal a fluctuating pattern in the employment rate with an increasing trend, while the unemployment rate shows a more variable pattern with a sharp increase during the COVID-19 pandemic. Factors such as education levels, economic growth, structural transformation, and institutional policies are identified as key determinants of employment dynamics. This research makes an important contribution in understanding the complexity of employment dynamics in Indonesia and highlights policy implications for promoting inclusive growth, improved job quality, and labour market resilience. The implications of this research are expected to serve as a foundation for policy formulation that is more adaptive and responsive to future challenges, creating a more inclusive and sustainable employment environment.